Introducing the Iterative Domain Green's Function Method for finite array analysis - Ludick, D.; Botha, M.; Davidson, David; Jakobus, U. (2016)
© 2016 IEEE. The purpose of this work Is to Introduce the Iterative Domain Green's Function Method (DGFM) that may be used for the analysis of large, disjoint finite antenna arrays. The iterative DGFM presents an improvement over the conventional DGFM in terms of accuracy. The convergence rate of the technique will be illustrated at the hand of an example.